Environmental filtering, competition, and facilitation in alpine and forestry plant communities in tropical mountains - Galván Cisneros, Carlos Mario (2024)
Understanding the mechanisms that influence the assembly of natural communities has become a central issue in ecological studies, especially because of the influence of diversity on ecosystem functioning. These mechanisms may be related to niche and neutral processes. Niche-related processes include selection imposed by the abiotic environment and biotic interactions, whereas neutral effects are related to chance or historical events. Mountain ecosystems are among the most suitable models for unraveling the interactions between the facets of biodiversity. The overall aim of this project was to understand the assembly processes of alpine and forest plant communities through phylogenetic and functional diversity across altitudinal gradients in tropical mountains. To respond to this approach, we selected areas from several tropical mountains worldwide. We used lists with altitude records from three tropical montane mountains of tropical ecosystems: Mount Puracé, Colombia; Mount Kilimanjaro, Tanzania; and Mount Haleakalā, Hawaii, USA (CAP. 1). In addition, six sampling sites were established along an elevation gradient of (3200-4100 m). At each station, 10 plots measuring 2.5 m x 4 m were established (CAP. 2 and 3). In addition, 28 isolated individuals of Espeletia lopezii (Asteraceae) were selected; a 70 cm diameter metal ring was centered on each caulescent rosette. In addition, 28 rings were established in the open areas (control) (CAP. 4). The alpha taxonomic diversity was estimated using Hill's numbers (q=0, q=1, q=2) (CAP. 2 and 4). For phylogenetic diversity, six phylogenetic metrics were calculated: lineage diversity as the total length of the phylogenetic branch (PD), mean pairwise phylogenetic distance (MPD), mean nearest taxon phylogenetic distance (MNTD), and standardized effect size of these metrics (CAP. 1, 2 and 4). To determine the functional responses that drive the assembly of communities along the elevation gradient, five functional traits were measured: leaf area, leaf length, leaf thickness, leaf dry matter content, and maximum plant height. The weighted community mean (CWM) of the traits and functional diversity (FD) were estimated (CAP. 3). Different statistical models were used to test the main effects of altitude and soil depth on taxonomic, phylogenetic, and functional metrics. In the three tropical mountains, an environmental filtering effect was observed with increasing altitude, causing phylogenetic clustering, decreasing phylogenetic diversity, and decreasing species richness. The decreasing phylogenetic distances between close relatives are congruent with neo-endemism, suggesting recent diversification of plants at high altitudes in tropical mountains, possibly driven by geographical isolation and environmental heterogeneity (CAP. 1). In Chapter 2, the results showed that as soil depth decreased and altitude increased, páramo plant communities showed a general pattern of decreasing phylogenetic diversity. These results are consistent with the general expectation that community assemblage attributes become more closely related as stressful environmental conditions increase along a gradient. In Chapter 3, the results showed that several functional traits (CWM) and several indices of functional diversity varied significantly along the altitude and soil gradient in the area. Three of the five functional traits showed the potential to describe how the functional composition of páramo communities responded to increasing environmental severity along these environmental gradients. The two functional diversity indices, FDis and FRic, significantly decreased with increasing elevation and decreasing soil depth. In Chapter 4, the vegetation under the canopy of the facilitator plants (E. lopezii) was found to have a positive impact on taxonomic diversity, compared to the control areas. Regarding phylogenetic diversity, the dominant pattern observed was mainly random. These results suggest that, at these altitudes, the metacommunity is strongly filtered by climatic and edaphic factors, and despite the benefits of the facilitation exerted by stem rosettes, it is difficult to detect a pattern of phylogenetic overdispersion. In Chapter 5, as a general trend, a greater number of species were found in locations at higher altitudes, decreasing in locations at lower altitudes, and where climatic seasonality is more marked and filters out species from lineages that are less tolerant to stressful environments. Nitrogen-fixing Fabaceae species were prominent among the important species, especially at low altitudes and more stressful sites. Keywords: Tropical mountains, altitudinal gradient, phylogenetic diversity, functional diversity, plant-plant interaction, community assembly.